Paleoanthropology And Orthodontıcs - T. Ufuk Toygar Memikoğlu; Hakan Gögen (Galenos Yayinevi, 1997)
The aim of this study was to evaluate the collaboration of paleoanthropology and orthodontics. Because medicine and dentistry are based on anatomy and/or physical anthropology, the relationship between these areas has been presented in a historical order.